Mapping the Global Landscape of Islamic Studies Research Using Bibliometric Analysis 2000–2024 - Judijanto, Loso (West Science Islamic Studies, 2026)
This study maps the global landscape of Islamic Studies research from 2000 to 2024 using bibliometric analysis. With the rapid expansion of Islamic Studies across disciplines, including theology, law, economics, and cultural studies, this research highlights significant shifts in both the volume and scope of scholarship. Drawing from databases like Scopus, the study reveals the central role of Southeast Asia, particularly Indonesia and Malaysia, in shaping the field, along with a growing academic presence in the Middle East, South Asia, and Africa. The study also uncovers emerging trends in Islamic finance, sustainability, and the intersection of Islamic principles with modern technological advancements, such as fintech and artificial intelligence. This comprehensive bibliometric map facilitates a deeper understanding of the regional contributions, thematic evolution, and collaboration networks that are defining the future of Islamic Studies.